Pauses Reﬂecting the Processing of Syntactic Units in Monolingual Text Production and Translation - Immonen, Sini; Mäkisalo, Jukka (HERMES - Journal of Language and Communication in Business, 2010)
This study explores how the process of translating relates to other types of writing processes by comparing pause lengths preceding syntactic units (words, phrases and clauses) in two types of writing task, a monolingual text production and a translation. It also discusses the grounds for interpreting pause length as a reﬂection of the cognitive demands of the writing process. The data was collected from 18 professional translators using the Translog keystroke logging software (Jakobsen/Schou 1999). Each subject wrote two texts: an expository text in Finnish and a translation from English into Finnish (Immonen 2006: 316-319). Firstly, phrase boundary pauses were categorised according to type, function and length of phrase. All three features correlate with pause length. On average, predicate phrases are preceded by short pauses, adpositional phrases by long pauses, and pauses preceding noun phrases grow with the length of the phrase. These ﬁ ndings suggest that the processing of the predicate begins before written production of the clause is started, whereas noun phrases and adpositional phrases are processed during writing. Secondly, pauses preceding clauses were categorised with respect to clause type. In monolingual text production, pauses preceding subordinate clauses are on average shorter than those leading to main clauses. In translation, pauses preceding subordinate and main clauses are almost the same length. It seems therefore that, in translation, the main clause and subordinate clause are processed separately despite the fact that the subordinate clause functions as a syntactic unit within the main clause.